The Effect of Midnight Temperature Maximum Winds on Post‐Midnight Equatorial Spread F - J. Krall; D. Hickey; J. D. Huba; P. B. Dandenault (Space Weather)
Abstract The SAMI3/equatorial spread F (Sami3 is also a model of the ionosphere/ESF) code is used to simulate the growth of equatorial plasma bubbles in the presence of a background wind field based on measured winds. The measured winds exhibit the well‐known “midnight temperature maximum” (MTM) pattern, in which an equatorward wind occurs simultaneously with a cessation in the zonal wind. The MTM is often preceded by strong equatorward winds (about 100 m/s). The circumstance where the MTM winds are symmetric across the equator is considered; here the meridional wind component in the southern hemisphere is the reverse of the northern meridional wind. The timing of the wind pattern relative to the imposition of a seed for the ESF instability is explored. We find that the simultaneous occurrence of a seed wave and a strong converging meridional wind pattern can produce post‐midnight ESF. We further find that the seed wave and the sudden cessation of the zonal winds can also produce post‐midnight ESF. The Magnetic mEridional NeuTrAl Thermospheric code verifies the occurrence of converging meridional wind patterns such as those simulated here, based on ionosonde data. Results suggest that regional‐scale wind measurements would aid in the prediction signal‐disrupting ionospheric bubbles.